Exploring the Existence of Innovative Work Behavior among Government Employee: Have Been There? - Dediek Tri Kurniawan; Yesiana Ihda Kusnayain; Fatwah Inna Aulisaina; Muhamad Arif Rahman Hakim (Journal of Indonesian Economy and Business, 2021)
Introduction/Main Objectives: This study aims to determine the existence of innovative work behavior ecosystems for Indonesia’s government employees Background problems: The quality of individual employees partially determines the quality of the organization. The abilities of the different employees who work in the same system will undoubtedly deliver the government employee and possibly produce results which are less than were expected. Novelty: The previous studies have examined innovative work behavior, focusing on the external factors and ignoring the internal factors of individual traits. This study focused on investigating the interrelationship among the factors that will be affected by innovative behavior, especially in government employees in Indonesia. Methods: This study examines the relationship among these variables using structural equation modeling (SEM) with LISREL 8.8 as the statistical tool. Finding/Result: This study found that transformational leadership and work engagement positively influence innovative work behavior. Unexpectedly, this research indicates an insignificant relationship between organizational justice and innovative work behavior among government employees. Besides, this study also found that transformational leadership and organizational justice have an impact on work engagement. Conclusion: These findings provide managerial implications about the need to strengthen employees’ innovative work behavior to ensure the organization’s continuity. Additionally, the results prove that innovative work behavior by government employees is supported by government’s role such as the style of leadership and work engagement.